Status of Vitamin D and Evaluation of Growth Parameters Seen in the Children Suffering from Thalassemia Major - Adnan Bashir, Khairjan Habib, Amanullah Lail, Mushtaque Ali Shah, Naseer Ahmed Memon, Zulfiqar Ali Dahri, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The objective of this research is to evaluate the growth metrics, as well as the levels of calcium, vitamin D, and phosphorus, in children diagnosed with beta-thalassemia major (BTM) who are undergoing treatment with packed red cell transfusions and chelation therapy. Study design: An analytical cross-sectional study Place and duration This study was conducted in Hamdard College of Medicine and Dentistry Karachi from March 2022 to March 2023. Methodology: In this study, 80 patients diagnosed with BTM, aged between 3 and 16 years, were meticulously compared to 80 children serving as the control group. The control group was selected to match the patients in terms of both sex and age. The study involved conducting anthropometric measurements and determining the serum levels of phosphorus, calcium, and vitamin D (specifically 25-hydroxycholecalciferol) for all the participants, both patients and controls. Results: Among the patients in our study, 49% exhibited short stature, and 47% were identified as underweight. Additionally, 43% of the patients had a low Body Mass Index (BMI). The mean total serum calcium level was measured at 6.5 ± 1.3 mg/dl, and the 25-hydroxycholecalciferol (25-OH Vit D) level was recorded at 10.5 ± 4.7 mcg/dl for our BTM patients group. In comparison, the control group had significantly higher mean levels of serum calcium (10.3 ± 1.1 mg/dl) and vitamin D (40.4±12.4 mcg/dl). The comparison of each shows statistical significance (P< 0.001). Conclusion: Children diagnosed with BTM commonly experience delays in growth and irregularities in metabolism, highlighting the crucial need for therapy. The observed metabolic disturbances are likely a result of iron overload and inadequate nutritional support. These factors underscore the significance of implementing appropriate treatments and nutritional strategies to address the health challenges faced by these children. Keywords: Calcium, Thalassemia major, Vitamin D deficiency, Growth, children